Potentials of Biochars Derived from Bamboo Leaf Biomass as Energy Sources: Effect of Temperature and Time of Heating - Bidayatul Armynah; Dahlang Tahir; Monalisa Tandilayuk; Zuryati Djafar; Wahyu H. Piarah (International Journal of Biomaterials)
Biochars from bamboo leaves as a potential energy resource were synthesized by annealing in the oxygen-free environment. Samples were characterized using proximate analysis, Fourier-transform infrared (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). Heating temperatures are 250°C, 300°C, and 350°C and for each temperature, the time was varied between 30, 60, and 90 minutes. The heating time for 30 minutes results in FC 30.777% and calorific value 15 MJ/Kg at temperature 250°C and decreased to 4.004% and 6 MJ/Kg at temperature 350°C, respectively. EDS shows the time of heating is an important parameter which shows the carbon and nitrogen contents were decreasing with the increase in the heating time, and silicon and oxygen contents were increasing with increase in the heating time. XRD shows broad (002) reflections between 20° and 30°, which indicated disordered carbon with small domains of coherent and parallel stacking of the graphene sheets, which is consistent with surface morphology of the SEM image. The experimental results indicated that heating at 300°C for 30 minutes is an effective and efficient parameter for fabrication of low-cost carbon from bamboo leaves which is a source of useful energy.